2022
DOI: 10.1002/fsn3.3044
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nutrient adequacy and associated factors among lactating women of rural Bangladesh using observed intake: Findings from Bangladesh Integrated Household Survey 2018–2019

Abstract: Lactating women of low‐ and middle‐income countries are prone to develop deficiencies in essential nutrients due to various demographic and socioeconomic components. This study aimed to estimate the adequacy of dietary intake and the determinants of diet quality of lactating women in rural Bangladesh. One‐day dietary recall (24‐Hour recall) data of 973 lactating women were obtained from the Bangladesh Integrated Household Survey (BIHS) 2018–2019. Nutrient adequacy was determined using the Estimated Average Req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
7
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 44 publications
(68 reference statements)
8
7
2
Order By: Relevance
“…Vitamin A intake inadequacy was prevalent among 86.7% of lactating mothers, according to this study. This is comparable to studies conducted in Ethiopia ( 13 ), Niger ( 12 ), and Bangladesh ( 8 ). In contrast, this study finding is lower than studies conducted in Bahir Dar City, Ethiopia ( 14 ), Zambia ( 11 ), China ( 45 ), and California ( 10 ), and higher than reports from studies conducted in Nigeria ( 46 ), Indonesia ( 41 ), Thailand ( 44 ) and Iran ( 43 ).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Vitamin A intake inadequacy was prevalent among 86.7% of lactating mothers, according to this study. This is comparable to studies conducted in Ethiopia ( 13 ), Niger ( 12 ), and Bangladesh ( 8 ). In contrast, this study finding is lower than studies conducted in Bahir Dar City, Ethiopia ( 14 ), Zambia ( 11 ), China ( 45 ), and California ( 10 ), and higher than reports from studies conducted in Nigeria ( 46 ), Indonesia ( 41 ), Thailand ( 44 ) and Iran ( 43 ).…”
Section: Discussionsupporting
confidence: 84%
“…This study revealed that the prevalence of micronutrient intake inadequacy among selected B vitamins (vitamin B1, vitamin B2, vitamin B3, vitamin B6, vitamin B9, and vitamin B12) ranges from 18.1 to 82.3%. Among lactating mothers, 33.7% of them had inadequate intake for vitamin B1 (Thiamin), which is higher than studies in Ethiopia ( 13 , 14 ), Iran ( 43 ), and California ( 10 ), and lower than findings from Zambia ( 11 ), Niger ( 12 ), Bangladesh ( 8 ), Thailand ( 44 ), China ( 45 ), and Indonesia ( 41 ). Dietary practices and mandatory fortification of staple foods have a major impact on thiamin intake; areas high in meat, whole grains, and legume production and consumption experience lower rates of inadequacy ( 48 ).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…A (581-643 μg vs. 321-328 μg) by adults greater than 18 years old was far higher than we had found in our present study (Fulgoni Iii & Agarwal, 2021), whereas the protein intake by Bangladesh lactating women was consistent with our findings, in which the median protein intake was 67.84 g (Islam et al, 2023).…”
Section: Average Dietary Energy and Nutrient Intakes Among Sport And ...supporting
confidence: 92%